Patterns of Dysgraphia in Primary Progressive Aphasia Compared to Post-Stroke Aphasia - Andreia V. Faria; Jenny Crinion; Kyrana Tsapkini; Melissa Newhart; Cameron Davis; Shannon Cooley; Susumu Mori; Argye E. Hillis (Behavioural Neurology)
We report patterns of dysgraphia in participants with primary progressive aphasia that can be explained by assuming disruption of one or more cognitive processes or representations in the complex process of spelling. These patterns are compared to those described in participants with focal lesions (stroke). Using structural imaging techniques, we found that damage to the left extrasylvian regions, including the uncinate, inferior fronto-occipital fasciculus, and sagittal stratum (including geniculostriate pathway and inferior longitudinal fasciculus), as well as other deep white and grey matter structures, was significantly associated with impairments in access to orthographic word forms and semantics (with reliance on phonology-to-orthography to produce a plausible spelling in the spelling to dictation task). These results contribute not only to our understanding of the patterns of dysgraphia following acquired brain damage but also the neural substrates underlying spelling.